Orchidea Selangoreana - wild orchids of Selangor - Go, Rusea (Jabatan Perhutanan Negeri Selangor and Kerajaan Negeri Selangor, 2014)
Publication based on real research findings and written in semi-scientific easy to read 210 pages containing 240 wild orchid species found in Selangor major forest reserves.